Comparison of the MDRD Study and CKD-EPI Equations for the Estimation of the Glomerular Filtration Rate in the Korean General Population: The Fifth Korea National Health and Nutrition Examination Survey (KNHANES V-1), 2010 - Tae-Dong Jeong; Woochang Lee; Sail Chun; Sang Koo Lee; Jin-Sook Ryu; Won-Ki Min; Jung Sik Park (Karger Publishers, 2013)
Background: We compared the accuracy of the Modification of Diet in Renal Disease (MDRD) study and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations in Korean patients and evaluated the difference in CKD prevalence determined using the two equations in the Korean general population. Methods: The accuracy of the two equations was evaluated in 607 patients who underwent a chromium-51-ethylenediaminetetraacetic acid GFR measurement. Additionally, we compared the difference in CKD prevalence determined by the two equations among 5,822 participants in the fifth Korea National Health and Nutrition Examination Survey, 2010. Results: Among the 607 subjects, the median bias of the CKD-EPI equation was significantly lower than that of the MDRD study equation (0.9 vs. 2.2, p=0.020). The accuracy of the two equations was not significantly different in patients with mGFR 2; however, the accuracy of the CKD-EPI equation was significantly higher than that of the MDRD study equation in patients with GFR ≥60 mL/min/1.73m2. The prevalences of the CKD stages 1, 2 and 3 in the Korean general population were 47.56, 49.23, and 3.07%, respectively, for the MDRD study equation; and were 68.48, 28.89, and 2.49%, respectively, for the CKD-EPI equation. Conclusions: These data suggest that the CKD-EPI equation might be more useful in clinical practice than the MDRD study equation in Koreans.